Guanidinoacetic acid supplementation and stocking density effects on broiler performance: behavior, biochemistry, immunity, and small intestinal histomorphology - Mohammad Alaa; Abeer Hamada Abdel Razek; Mohamed Ahmed Tony; Aya Mohye Yassin; Mohamad Warda; Mohamed Ahmed Awad; Basma Mohamed Bawish (Acta Veterinaria Scandinavica)
Abstract Background Rearing poultry under stressful high stocking density (HSD) conditions is a common commercial practice to increase profitability, despite its negative effects on broiler physiology and welfare. Many feed additives are used to alleviate the negative impact of such practices. This study investigated the ameliorative effects of guanidinoacetic acid (GAA) on growth performance, ingestive behavior, immune response, antioxidant status, stress indicators, and intestinal histomorphometry of broilers subjected to HSD. A total of 364 male broilers were randomly allocated into four treatments with 7 replicates each in a 2 × 2 factorial arrangement: two stocking densities (SD) (10 and 16 birds/m2) and two GAA levels (0 and 0.6 g/kg feed). Results Body weight, weight gain, feed intake, feed conversion ratio, production efficiency factor, dressing yield, and ingestive behavior were negatively affected by HSD, whereas the mortality rate was unaffected (P > 0.05). GAA improved the overall growth performance and dressing percentage (P < 0.05). In the HSD group, the immune response decreased at d 21 (P < 0.05). Creatine kinase, glutathione peroxidase (GPX), superoxide dismutase, catalase, triglycerides, and villus length and width (ileum) were reduced, whereas corticosterone (CORT) was increased (P < 0.05). Moreover, GAA increased the hemagglutination-inhibition titer at 21 days and the levels of lactate dehydrogenase, GPX, and catalase and decreased the levels of creatinine, alanine aminotransferase, nitrite, triglycerides, and CORT (P < 0.05). SD and GAA did not affect malondialdehyde or other biochemical parameters (P > 0.05). Conclusions Dietary GAA supplementation can improve productivity and antioxidant status and reduce stress in broilers reared in a HSD environment.